Antitumor Activity of Species of the Genus Artemisia L.: Current State and Prospects (Review) - Yu. V. Romanteeva; M. A. Berezutsky; M. N. Kurchatova (Разработка и регистрация лекарственных средств, 2023)
Introduction. Recently, the anticancer activity of representatives of the genus Artemisia L. has been actively studied, and most studies are devoted to Artemisia annua L., which has been used since ancient times in the folk medicine of several countries as an antimalarial and anticancer agent. The similarity of the chemical composition predetermines the study of the anticancer activity of other species of the genus Artemisia L. The information about this is still not fully presented in scientific publications, is very diverse and sometimes even contradictory. Review of modern studies of anticancer activity of species of the genus Artemisia L., generalization of available data and providing information for future research is relevant.Text. The article presents a review of experimental data on the study of anticancer activity of representatives of the genus Artemisia L. It is noted that the main mechanism of such activity is apoptosis. Apoptosis is triggered by the increase of reactive oxygen species (ROS) inside cancer cells, reduction of mitochondrial membrane potential, activation of pro-apoptotic and, on the contrary, inhibition of anti-apoptotic proteins, as well as by formation of membrane bubbles, cell compression and by activation caspase.Conclusion. In the presented review, about 30 species of the genus Artemisia L. With the presented degree of study of this area, a number of questions remain unresolved. The most studied with respect to cytotoxic activity are Artemisia absinthium L. and Artemisia vulgaris L. In this aspect, the study of other closely related species of the genus Artemisia L. Also relevant is the study of cytotoxicity of representatives of the genus Artemisia L. on normal cell cultures and in comparison with positive control. In addition, a detailed study of the pool of secondary metabolites of different species of the genus Artemisia L. remains significant in order to reliably determine the components responsible for the manifestation of anticancer action. The pronounced effectiveness against cancer cells and, at the same time, a weak effect on healthy cells of the body of representatives of the genus Artemisia L. opens up the prospect of their use as sources of partner drugs with a synergistic effect and means of augmentation of antitumor therapy.